Analysis of Patterns and Drag of Tandem Minibus Models in Various Configurations - Wawan Rauf; Rahmad Hidayat Boli; Sahional Ishak; Novriyanti Talango (The Indonesian Institute of Science and Technology Research, 2026)
The flow through three mini buses arranged in tandem is one type of fluid flow in infrastructure and transportation engineering. The characteristics of the flow pattern formed in each vehicle have an influence on the flow pattern formed in other vehicles. The purpose of this study is to analyze the drag coefficient and characteristics of the flow pattern in models in various configurations and distances between models. The test was conducted by applying experimental methods and numerical computation to obtain the characteristics of the flow pattern. Specifically to obtain the results of the drag coefficient, the method used was only numerical computation. The results of the study showed that the distance between the M/D models influenced the flow pattern formed in all configurations. The smallest drag coefficient for each configuration 1 Cd = 1.43285 at M/D = 0.03, Configuration 2 Cd = 0.80341 at M/D = 0.01, and configuration 3 Cd = 0.77911 at M/D = 0.03 as well as the model with the lowest drag compared to all distances in configuration 1 and configuration 2.